Neurostimulation device for ameliorating salivary dysfunction: A novel neuromodulatory perspective - Rajkumar Krishnan; Nagarathinam Anbu Elangovan; Ramya Ramadoss (Oral Oncology Reports)
Xerostomia, or dry mouth, is a condition characterised by a decrease in salivary flow rate, affecting the quality of life of many individuals. Factors contributing to xerostomia include radiation therapy, pathologies, medications, and age-related loss of salivary gland function. Traditional management approaches have focused on pharmacological interventions and symptom relief; however, innovative therapies are needed to address the underlying causes of salivary gland dysfunction. Neurostimulation is a rapidly evolving field that holds promise for managing xerostomia by targeting the neural pathways involved in salivary secretion. Studies have shown the efficacy of transcutaneous electrical stimulation in enhancing salivary secretion by selectively activating the nerves innervating the salivary glands. Neurostimulation offers a targeted and personalised approach to treatment, allowing for precise modulation of salivary gland function based on individual patient needs. Neurostimulation devices for xerostomia include the biosonics-SAL salivator system, AdvanTeq 2000, GenNarino, Mediheightec 8000, and the custom extraoral wearable device developed by Rajkumar et al. Neurostimulation is a promising therapeutic approach for managing xerostomia; however, further research is needed to validate the underlying mechanisms and optimise neurostimulation techniques for optimal salivary secretion.